Lotus notes and domino 6. Programming bible - Benz, Brian; Oliver, Rocky
* Covers all the programming techniques, concepts, and languages used with Notes and Domino, as well as the many new features of Domino 6 * Thoroughly examines the Notes and Domino role with Java, XML, Web services, and other IBM products and technologies * Provides extensive code and examples, many geared to the needs of administrators * High-profile authors, known to their audience through conferences and articles * Companion Web site shows example applications from the book running on a live Domino server and provides code download